P100 Real-world data: the incidence, diagnosis, and management outcomes of patients with immunotherapy-related colitis in two tertiary centres. (25th January 2019) - Cheung, V; Gupta, T; Olsson-Brown, A; Subramanian, S; Payne, M; Middleton, M; Brain, O
Abstract: Background: Checkpoint inhibitors are a novel anti-cancer therapy that are standard of care in metastatic melanoma, non-small cell lung and renal cancer. CTLA-4 inhibitors (eg, Ipilimumab) and PD-1 inhibitors (Nivolumab, Pembrolizumab) can be used separately or in combination for melanoma, whereas single PD-1 inhibitors are the norm for others. Their immune inhibition is non-specific, leading to a number of immune-related adverse events (irAEs), including colitis, hepatitis, and pancreatitis. Combination therapy is known to cause more irAEs than single-agent PD-1 inhibition. There are limited real-world clinical data describing the incidence and management of these GI irAEs. Methods: Retrospective two–centre (John Radcliffe Hospital in Oxford and Clatterbridge Cancer Centre in Liverpool) review. Melanoma, renal and lung cancer patients receiving Ipilimumab ± Nivolumab ± Pembrolizumab between December 2011 and June 2018 were identified from the oncology prescribing database. The electronic patient record (EPR) was used to determine the incidence of GI side effects. Investigations, treatment, and outcome data were collated. Results: Of 1125 patients who had immunotherapy, 130 developed colitis (11.6%). In our cohort: (1) Median age was 66 (Males- Median 67, range 24–88; females: 64.5 range 27–86); (2) 60% were male; (3) 63.0% patients required admission (75% combination); (4) median length of admission is 4–7 days (6 combination); (5) presence of erosions or ulcers at endoscopy tended to predict a more severe outcome; (6) faecal calprotectin in steroid refractory cases was >300 in all patients where measured; (7) high proportion of patients receiving IV methylprednisolone 43.8% (66.7% combination); (8) significant proportion of patients requiring infliximab 21.5% (35% in combination therapy); (9) of those requiring infliximab, 64.3% (18/28) were male; (10) two patients with refractoriness to steroids and infliximab had vedolizumab; (11) colectomy rate 2.3% (3/130). Complete management and outcome data will be presented. Conclusions: Immunotherapy-related colitis is one of the more severe adverse events related to immunotherapy and a significant proportion of patients will require hospital admission. Steroid refractoriness is a significant problem and studies are required to elucidate optimum treatment regimens and escalation strategies. This has implications for standardisation of care and healthcare provision on already stretched budgets. Complete management and outcome data will be presented.